Method and application of in-situ growth of ultra-thin aluminum oxide protective layer on the surface of wurtzite aluminum nitride-based film

By growing at the surface of the surface of the aluminum nitrogen-nitrogen-nitrogen-nitrogen-nitrogen-nitrogen-nitrogen-nitrogen-nitrogen-nitrogen-nitrogen-nitrous film, a super thin aluminum protective layer of 2-5 nanometer thickness solves the problem of moisture and oxidation problems before preparing the metal electrodes of the metal. The leakage current and increase the anti -strike voltage.

CN115725945BActive Publication Date: 2025-01-24DALIAN CHIP MATERIALS & THIN FILM TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211423062.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-15
Publication Date
2025-01-24
Estimated Expiration
2042-11-15

AI Technical Summary

Technical Problem

Worzinite aluminum nitride-based film is prone to deliques and oxidation before preparing the metal upper electrode, resulting in an interface layer with high oxygen impurities and nitrogen vacancy with the upper electrode, increasing leakage current and reducing breakdown resistance.

Method used

The ultra-thin alumina protective layer of 2-5 nanometer thick in the same vacuum cavity room is oxidized to the Al2O3 layer by oxidizing the metal AL thin film on the surface of the ALN basal film on the surface of the ALN basal film to fully cover the ALN basal film.

Benefits of technology

Effectively avoid the moisture oxidation of the Aln -based thin film, reduce the leakage current of the device, increase the anti -strike voltage, and ensure the work voltage of the Aln base pressure electro -electric film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115725945B_ABST
    Figure CN115725945B_ABST
Patent Text Reader

Abstract

A method and application for in-situ growth of an ultra-thin aluminum oxide protective layer on the surface of a wurtzite aluminum nitride-based film, belonging to the field of electronic information technology. The present invention utilizes the same Al metal target to in-situ grow a metal Al film on the surface of a wurtzite AlN-based film, and then in-situ oxidizes the metal Al film into an ultra-thin and dense Al2O3 layer to completely cover and protect the AlN-based piezoelectric and ferroelectric films thereunder. The present invention can solve the deliquescent oxidation problem of the AlN-based film during the subsequent growth of a graphic upper electrode, is easy to operate, and has strong engineering practicality; at the same time, the present invention utilizes the excellent dielectric properties of the Al2O3 layer and the voltage division principle of a series capacitor to reduce the leakage current of the device, improve the breakdown voltage, and ensure the working voltage division of the AlN-based piezoelectric and ferroelectric films, and has broad application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of electronic information technology, and relates to a method and application of in-situ growing of an ultra-thin aluminum oxide protective layer on the surface of a wurtzite aluminum nitride-based film. Background Art

[0002] Wurtzite AlN films with crystal plane texture (c-axis preferred growth orientation) are widely used in high-frequency surface acoustic wave (SAW) filters, bulk acoustic wave (BAW) filters, MEMs sensors and other devices due to their excellent piezoelectric properties, high breakdown field strength, high thermal conductivity, high temperature stability, high acoustic wave transmission rate and other characteristics. In recent years, Sc doping has been found to significantly improve the piezoelectric properties of AlN films; in addition, wurtzite AlN films doped with elements such as Sc, B, and Y have also been shown to have excellent ferroelectric properties and can be used in the preparation of devices such as ferroelectric enhanced high electron mobility transistors and ferroelectric memories.

[0003] Wurtzite AlN-based films for piezoelectric and ferroelectric devices are generally first deposited on single crystal substrates such as silicon, sapphire, and gallium nitride, or on bottom electrode films such as platinum (Pt), molybdenum (Mo), titanium nitride (TiN), and tantalum nitride (TaN) with (111) textures grown on the substrate surface. The heteroepitaxial crystal plane of the single crystal substrate or the (111) crystal plane texture of the bottom electrode film is used to induce the wurtzite AlN-based film to have a (0002) textured structure; then a patterned metal top electrode is prepared on the surface of the AlN-based film using a hard mask or a photolithography process. Before preparing the metal top electrode, the AlN-based film has to be removed from the vacuum environment and exposed to the atmosphere for a short period of time. Studies have shown that the surface of AlN is extremely active and easily absorbs water vapor in the air to undergo a hydrolysis reaction AlN+3H2O=Al(OH)3↓+NH3↑, and reacts with oxygen in the air to form aluminum nitride oxide (AlN 1-x O x The above reaction leads to the appearance of an interfacial layer with a thickness of several nanometers and rich in high concentration of oxygen impurities and nitrogen vacancies between the AlN-based film and the subsequently grown upper electrode. Oxygen and nitrogen vacancies act as donor doping to give the interfacial layer n + Due to the degenerate semiconductor characteristics, the electrons emitted by the metal upper electrode can tunnel through the interface layer into the AlN-based film, resulting in increased leakage current and poor breakdown resistance of the device. How to overcome the surface deliquescence and oxidation of the AlN-based film and avoid the appearance of an interface layer with a high oxygen donor doping concentration between the upper electrode has become a problem that needs to be solved urgently to improve device performance and service reliability. Summary of the invention

[0004] In order to solve the above problems, the present invention proposes to use physical vapor deposition (PVD) to continuously grow (0002) textured wurtzite aluminum nitride-based piezoelectric and ferroelectric films and ultra-thin aluminum oxide protective layers in the same vacuum chamber. The specific method is to first use Al as the main component target, Sc, Y, B, etc. as doping element targets, and use magnetron sputtering or laser pulse technology to deposit AlN-based piezoelectric and ferroelectric films with (0002) textured organizational structures on a single crystal substrate or a substrate with a (111) textured bottom electrode film in an Ar and N2 mixed atmosphere or a pure N2 atmosphere. Subsequently, using single Al metal as the target material, in a pure Ar atmosphere, magnetron sputtering or laser pulse technology is used to in-situ deposit a metal Al film with a thickness of 2-5 nanometers on the surface of the AlN-based film. Finally, the metal Al film is subjected to in-situ oxidation treatment in the same vacuum chamber to transform it into an amorphous, dense Al2O3 thin layer that completely covers the AlN-based piezoelectric and ferroelectric film underneath.

[0005] Al2O3 film has excellent chemical stability and will not react with water vapor in the atmosphere or the upper electrodes such as metals and transition metal nitrides to be prepared later. At the same time, the band gap of Al2O3 film is as high as 8.9eV (higher than 6.2eV of AlN). After contacting with the upper electrode, it will form a Schottky contact with a very high barrier height. According to semiconductor physics theory, this type of interface contact can greatly reduce leakage current and improve the device's breakdown voltage. The relative dielectric constant (ε r ) is 9, which is almost the same as AlN. The thickness of the Al2O3 film prepared by the present invention is 2-5 nanometers, while the thickness of the AlN-based film with excellent piezoelectric and ferroelectric properties is generally greater than 50 nanometers. When forming a metal-Al2O3 film / AlN-based film-metal (MIM) structure device, the capacitor (C1) formed by the Al2O3 film and the capacitor (C2) formed by the AlN-based film are in a series relationship with equal areas. The capacitance formula is C=ε0ε r A / d, where A is the area of ​​the capacitor, d is the thickness of the dielectric film, ε0 is the vacuum dielectric constant, ε r is the relative dielectric constant of the dielectric film. Since the thickness of the Al2O3 film is much smaller than that of the AlN-based film, C1 is much larger than C2. According to the voltage-dividing principle of the series capacitor, most of the applied voltage will be applied to the AlN-based film (>90%), and the voltage-dividing of the Al2O3 film is extremely small, thus ensuring the piezoelectric and ferroelectric properties of the AlN-based film and avoiding the breakdown of the Al2O3 film.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0007] A method for in-situ growth of an ultra-thin aluminum oxide protective layer on the surface of a wurtzite aluminum nitride-based film, wherein a metal Al film is in-situ grown on the surface of a wurtzite AlN-based film using the same Al metal target, and then the metal Al film is in-situ oxidized into an ultra-thin and dense Al2O3 layer to completely cover and protect the AlN-based piezoelectric and ferroelectric films thereunder, thereby solving the deliquescent oxidation problem of the AlN-based film during the subsequent growth of a graphic upper electrode, and the operation is simple and easy, and the engineering practicability is strong. At the same time, the excellent dielectric properties of the Al2O3 layer and the voltage-dividing principle of a series capacitor are utilized to reduce the leakage current of the device, improve the breakdown voltage, and ensure the working voltage-dividing of the AlN-based piezoelectric and ferroelectric films, and the physical mechanism is clear and distinct.

[0008] A method for in-situ growing an ultra-thin aluminum oxide protective layer on the surface of a wurtzite aluminum nitride-based film, specifically comprising the following steps:

[0009] Step 1: Place the cleaned single crystal substrate or the substrate with a (111) textured bottom electrode film grown on the surface on a sample stage of a vacuum device.

[0010] The single crystal substrate is made of one of III-V semiconductor materials such as sapphire, Si, Ge or GaN.

[0011] The (111) textured bottom electrode film includes one of platinum (Pt), molybdenum (Mo), titanium nitride (TiN), tantalum nitride (TaN), etc., and has a thickness of 50-150nm.

[0012] Step 2: The same Al metal target is used throughout the process, and Sc, Y, B, etc. are added as doping element targets. In an Ar, N2 mixed atmosphere or a pure N2 atmosphere, a wurtzite AlN-based piezoelectric and ferroelectric film with a (0002) textured structure is deposited on the substrate of step (1) by magnetron sputtering technology. Subsequently, in the same chamber, in a pure Ar atmosphere, a metal Al film with a thickness of 2-5 nanometers is in situ deposited on the surface of the AlN-based film by magnetron sputtering technology. Finally, the metal Al film is subjected to in-situ oxidation treatment in the same vacuum chamber to transform it into an amorphous, dense Al2O3 thin layer that completely covers the wurtzite AlN-based piezoelectric and ferroelectric film underneath.

[0013] The magnetron sputtering technology can be replaced by laser pulse deposition technology and the like.

[0014] The thickness of the AlN-based film is 50-1500nm.

[0015] The thickness of the Al2O3 thin layer is 2-5nm

[0016] The specific process parameters for depositing wurtzite aluminum nitride-based films with (0002) textured microstructures are as follows: target-substrate distance is 80-120 mm; Ar:N2=(0-20):(20-50)sccm; sputtering power: 50-300W; substrate temperature is room temperature to 400°C; working gas pressure is 0.4 to 0.8Pa; sputtering time: 30-200min.

[0017] The specific process parameters for depositing a metal aluminum film on the surface of an aluminum nitride-based film are as follows: the target material is a single metal aluminum target, the target-substrate distance is 80-120 mm; the Ar gas flow rate is 20-50 sccm; the sputtering power is 50-80 W; the substrate temperature is room temperature to 400°C; the working gas pressure is 0.4 to 0.8 Pa; and the sputtering time is 1-3 min.

[0018] The in-situ oxidation treatment process includes thermal oxidation by introducing high-purity oxygen into the vacuum chamber and heating the sample stage, and plasma oxidation by discharging and ionizing the high-purity oxygen introduced into the vacuum chamber.

[0019] The specific process parameters of the in-situ treatment are: the vacuum chamber is maintained at a negative pressure state lower than one atmosphere, the substrate temperature is room temperature to 400°C, and the oxidation time is 1-3 minutes.

[0020] An application of in-situ growth of an ultra-thin aluminum oxide protective layer on the surface of a wurtzite aluminum nitride-based film, using thermal evaporation or sputtering to prepare a top electrode on a substrate on which a wurtzite AlN-based piezoelectric or ferroelectric film with a (0002) textured organizational structure has been deposited, and a metal-dielectric-metal (MIM) structure capacitor is obtained for a sample with a bottom electrode grown on the substrate surface, and the piezoelectric ferroelectric properties of the capacitor are tested using a piezoelectric ferroelectric tester.

[0021] The top electrode is made of one of highly conductive metals such as Au, Pt, Al, Cu and TiN.

[0022] The thickness of the top electrode is 80-150nm.

[0023] The beneficial effects of the present invention are as follows: the present invention provides a method for in-situ growing an ultra-thin aluminum oxide protective layer on the surface of a wurtzite aluminum nitride-based film for an electronic device, wherein a metal Al film is in-situ grown on the surface of a wurtzite AlN-based film using the same Al metal target, and then the metal Al film is in-situ oxidized into an ultra-thin and dense Al2O3 layer to completely cover and protect the AlN-based piezoelectric and ferroelectric films thereunder. The method not only solves the deliquescent oxidation problem of the wurtzite AlN-based film during the subsequent growth of a graphic upper electrode, but is also simple and easy to operate and has strong engineering practicality. At the same time, the excellent dielectric properties of the Al2O3 layer and the voltage-dividing principle of a series capacitor are utilized to reduce the leakage current of the device, improve the breakdown voltage, and ensure the working voltage-dividing of the AlN-based piezoelectric and ferroelectric films, and the physical mechanism is clear and distinct. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 A flow chart of in-situ growth of an ultra-thin aluminum oxide protective layer on the surface of a (0002) textured wurtzite aluminum nitride-based film in the method of the present invention;

[0025] Figure 2 In Comparative Example 1, (111) textured Pt is used as the bottom electrode and the top electrode, and (0002) textured wurtzite Al 0.9 Sc 0.1 Leakage current curve of N film sample;

[0026] Figure 3 In Example 1, (111) textured Pt was used as the bottom electrode and the top electrode, and (0002) textured wurtzite Al 0.9 Sc 0.1 Leakage current curve of the sample with in-situ growth of ultra-thin aluminum oxide protective layer on the surface of N film. DETAILED DESCRIPTION

[0027] In order to make the purpose, technical solution and advantages of the present invention clearer, the operation process of the present invention is further described in detail below with reference to the accompanying drawings and specific examples. It should be noted that the specific examples described herein are only used to explain the present invention, and the illustrations are for schematic purposes only and are not intended to limit the scope of the present invention.

[0028] Comparative Example 1

[0029] In this comparative example, a single crystal silicon substrate was selected as the substrate and cleaned using the semiconductor industry standard RCA cleaning process. Using DC magnetron sputtering technology, the target material was platinum. Under the conditions of a target-substrate distance of 80 mm, an Ar gas flow rate of 40 sccm, a DC sputtering power of 150 W, a substrate temperature of 100 ° C, a working gas pressure of 0.4 Pa, and a sputtering time of 10 min, a layer of Pt film with a thickness of 100 nm and a (111) texture was grown. Then, using RF magnetron sputtering technology, the target materials were aluminum and scandium targets, the RF sputtering powers were 170 and 30 W respectively, the target-substrate distance was 80 mm, the nitrogen flow rate was 50 sccm, the substrate temperature was 200 ° C, the working gas pressure was 0.4 Pa, and the sputtering time was 80 min, a layer of Al with a thickness of 300 nm and a (0002) texture was grown. 0.9 Sc 0.1 N film. Then, a 150nm Pt top electrode was prepared by thermal evaporation to obtain a MIM capacitor, and the leakage current of the capacitor was tested using a ferroelectric tester.

[0030] Figure 2 This is the leakage current curve of the prepared capacitor sample. As can be seen from the figure, when the electric field strength is 1MV / cm, the leakage current density is 1.3×10 -5 A / cm 2 , indicating that Al 0.9 Sc 0.1 The N film capacitor sample has a larger leakage current. The reason is that Al 0.9 Sc 0.1 The surface of the N film deliquesces and oxidizes, and an interface layer with high oxygen impurity and nitrogen vacancy donor doping concentration appears between the upper electrode. Electrons tunnel through the interface layer into the AlN-based film, resulting in an increase in leakage current.

[0031] Example 1

[0032] In this embodiment, a single crystal silicon substrate is selected as the substrate and is cleaned using the semiconductor industry standard RCA cleaning process. A DC magnetron sputtering technique is used, the target material is platinum, and a layer of Pt film with a thickness of 100nm and a (111) texture is grown under the conditions of a target-substrate distance of 80mm, an Ar gas flow rate of 40sccm, a DC sputtering power of 150W, a substrate temperature of 100°C, a working gas pressure of 0.4Pa, and a sputtering time of 10min. Then, an RF magnetron sputtering technique is used, the target materials are aluminum and scandium targets, the RF sputtering powers are 170 and 30W respectively, the target-substrate distance is 80mm, the nitrogen flow rate is 50sccm, the substrate temperature is 200°C, the working gas pressure is 0.4Pa, and the sputtering time is 80min, a layer of Al with a thickness of 300nm and a (0002) texture is grown. 0.9 Sc 0.1N film. Then, magnetron sputtering technology was continued in the same chamber, the nitrogen source was turned off, the argon flow rate was set to 20 sccm, the aluminum target sputtering power was 50 W, the substrate temperature was 200 ° C, the working pressure was 0.4 Pa, and the sputtering time was 1 min. 0.9 Sc 0.1 A 2nm thick Al film was grown in situ on the surface of the N film. Then the sputtering was stopped, the argon source was turned off, 5sccm of high-purity oxygen was introduced, the pressure was kept at 0.4Pa, the substrate temperature was 200℃, and the oxidation time was 1min, to obtain an Al2O3 film with a thickness of about 2nm. A 150nm Pt top electrode was prepared by thermal evaporation to obtain a MIM capacitor, and the leakage current of the capacitor was tested using a ferroelectric tester.

[0033] Figure 3 This is the leakage current curve of the prepared capacitor sample. As can be seen from the figure, when the electric field strength is 1MV / cm, the leakage current density is 7.1×10 -7 A / cm 2 , indicating that Al2O3 protective layer 0.9 Sc 0.1 The leakage current of the N sample is significantly reduced. Compared with the Al2O3 protective layer in Comparative Example 1, the 0.9 Sc 0.1 N film, the present invention adopts in-situ growth of Al2O3 protective layer to make Al 0.9 Sc 0.1 The leakage current density of N-film capacitors is reduced by two orders of magnitude.

[0034] Example 2

[0035] In this embodiment, a single crystal silicon substrate is selected as the substrate and is cleaned using the semiconductor industry standard RCA cleaning process. A DC magnetron sputtering technique is used, the target material is platinum, and a layer of Mo film with a thickness of 50nm and (111) texture is grown under the conditions of a target-substrate distance of 80mm, an Ar gas flow rate of 30sccm, a DC sputtering power of 120W, a substrate temperature of 300°C, a working gas pressure of 0.5Pa, and a sputtering time of 8min. Then, an RF magnetron sputtering technique is used, the target materials are aluminum and scandium targets, the RF sputtering power is 300W, the target-substrate distance is 100mm, the nitrogen and argon gas flows are both 20sccm, the substrate temperature is room temperature, the working gas pressure is 0.5Pa, and the sputtering time is 200min, a layer of Al with a thickness of 1500nm and (0002) texture is grown. 0.6 Sc 0.4 N film. Then, magnetron sputtering technology was continued in the same chamber, the nitrogen source was turned off, the argon flow rate was set to 30sccm, the aluminum target sputtering power was 70W, the substrate temperature was room temperature, the working gas pressure was 0.5Pa, and the sputtering time was 2min.0.6 Sc 0.4 A 3nm thick Al film was grown in situ on the surface of the N film. Then the sputtering was stopped, the argon source was turned off, and 10sccm of high-purity oxygen was introduced. The gas pressure was kept at 0.5Pa, the substrate temperature was still at room temperature, and the oxidation time was 2min. An Al2O3 film with a thickness of about 3nm was obtained. A 100nm Au top electrode was prepared by evaporation to obtain a MIM capacitor. The leakage current of the capacitor was tested using a ferroelectric tester. When the electric field strength was 1MV / cm, the leakage current density was 4.02×10 -7 A / cm 2 .

[0036] Example 3

[0037] In this embodiment, a single crystal silicon substrate is selected as the substrate and is cleaned using the semiconductor industry standard RCA cleaning process. A DC magnetron sputtering technique is used, the target material is platinum, and a layer of Pt film with a thickness of 150nm and a (111) texture is grown under the conditions of a target-substrate distance of 80mm, an Ar gas flow rate of 40sccm, a DC sputtering power of 150W, a substrate temperature of 100°C, a working gas pressure of 0.3Pa, and a sputtering time of 15min. Then, an RF magnetron sputtering technique is used, the target materials are aluminum and scandium targets, the RF sputtering powers are 150 and 50W respectively, the target-substrate distance is 120mm, the nitrogen flow rate is 50sccm, the substrate temperature is 400°C, the working gas pressure is 0.8Pa, and the sputtering time is 30min, to grow a layer of Al with a thickness of 50nm and a (0002) texture. 0.7 Sc 0.3 N film. Then, magnetron sputtering technology was continued in the same chamber, the nitrogen source was turned off, the argon flow rate was set to 50sccm, the aluminum target sputtering power was 80W, the substrate temperature was 400℃, the working pressure was 0.8Pa, and the sputtering time was 3min. 0.7 Sc 0.3 A 5nm thick Al film was grown in situ on the surface of the N film. Then the sputtering was stopped, the argon source was turned off, 10sccm of oxygen was introduced, the gas pressure was maintained at 0.7Pa, the substrate temperature was still 400℃, and the oxidation time was 3min, resulting in an Al2O3 film with a thickness of about 5nm. An 80nm TiN top electrode was prepared by magnetron sputtering to obtain a MIM capacitor. The leakage current of the capacitor was tested using a ferroelectric tester. When the electric field strength was 1MV / cm, the leakage current density was 1.6×10 -7 A / cm 2 .

[0038] The above embodiments are only used to illustrate but not to limit the technical solutions of the present invention. Any technical solutions that do not deviate from the spirit and scope of the present invention should be included in the scope of the patent application of the present invention.

Claims

1. A method for in-situ growth of an ultra-thin aluminum oxide protective layer on the surface of a wurtzite aluminum nitride-based film, characterized in that: The method uses the same Al metal target to in-situ grow a metal Al film on the surface of a wurtzite AlN-based film, and then in-situ oxidizes the metal Al film into an ultra-thin and dense Al2O3 layer to completely cover and protect the AlN-based piezoelectric and ferroelectric films thereunder, thereby obtaining an ultra-thin aluminum oxide protective layer in-situ grown on the surface of the wurtzite aluminum nitride-based film; the method comprises the following steps: Step 1: placing a cleaned single crystal substrate or a substrate with a (111) textured bottom electrode film grown on its surface on a sample stage of a vacuum device; Step 2: The same Al metal target is used throughout the process, and Sc, Y, and B are added as doping element targets. In an Ar and N2 mixed atmosphere or a pure N2 atmosphere, a wurtzite AlN-based piezoelectric and ferroelectric film with a (0002) textured organizational structure is deposited on the substrate of step 1 using magnetron sputtering technology; subsequently, in the same chamber, in a pure Ar atmosphere, a metal Al film with a thickness of 2-5 nanometers is in situ deposited on the surface of the AlN-based film using magnetron sputtering technology; finally, the metal Al film is in situ oxidized in the same vacuum chamber to transform it into an amorphous, dense Al2O3 thin layer that completely covers the wurtzite AlN-based piezoelectric and ferroelectric film underneath; the thickness of the Al2O3 thin layer is 2-5nm.

2. The method for in-situ growing an ultra-thin aluminum oxide protective layer on the surface of a wurtzite aluminum nitride-based film according to claim 1, characterized in that: The magnetron sputtering technology can be replaced by laser pulse deposition technology.

3. The method for in-situ growing an ultra-thin aluminum oxide protective layer on the surface of a wurtzite aluminum nitride-based film according to claim 1, characterized in that: The single crystal substrate is made of sapphire, Si, Ge, GaN or other III-V semiconductor materials; the (111) textured bottom electrode film includes one of platinum, molybdenum, titanium nitride and tantalum nitride, and has a thickness of 50-150nm.

4. The method for in-situ growing an ultra-thin aluminum oxide protective layer on the surface of a wurtzite aluminum nitride-based film according to claim 1, characterized in that: The thickness of the AlN-based film is 50-1500nm.

5. The method for in-situ growing an ultra-thin aluminum oxide protective layer on the surface of a wurtzite aluminum nitride-based film according to claim 1, characterized in that: Process parameters include target-substrate distance, ratio of argon to nitrogen, sputtering power, substrate temperature, and working gas pressure: The process parameters for depositing a wurtzite aluminum nitride-based film with a (0002) textured structure are as follows: target-substrate distance is 80-120 mm; Ar:N2=(0-20):(20-50)sccm; sputtering power: 50-300 W; substrate temperature is room temperature to 400° C.; working gas pressure is 0.4 to 0.8 Pa; sputtering time: 30-200 min; The specific process parameters for depositing a metal aluminum film on the surface of an aluminum nitride-based film are as follows: the target material is a single metal aluminum target, the target-substrate distance is 80-120 mm; the Ar gas flow rate is 20-50 sccm; the sputtering power is 50-80 W; the substrate temperature is room temperature to 400°C; the working gas pressure is 0.4 to 0.8 Pa; and the sputtering time is 1-3 min.

6. The method for in-situ growing an ultra-thin aluminum oxide protective layer on the surface of a wurtzite aluminum nitride-based film according to claim 1, characterized in that: The in-situ oxidation process is thermal oxidation in which high-purity oxygen is introduced into the vacuum chamber and heated by the sample stage, and plasma oxidation in which the high-purity oxygen introduced into the vacuum chamber is discharged and ionized; The process parameters of the in-situ oxidation treatment are as follows: the vacuum chamber is maintained at a negative pressure state lower than one atmosphere, the substrate temperature is room temperature to 400° C., and the oxidation time is 1-3 minutes.

7. An application of in-situ growth of an ultra-thin aluminum oxide protective layer on the surface of a wurtzite aluminum nitride-based film, characterized in that: The protective layer is prepared by the method described in any one of claims 1 to 6, and a top electrode is prepared on a substrate on which a wurtzite AlN-based piezoelectric or ferroelectric film having a (0002) textured organizational structure has been deposited by thermal evaporation or sputtering. For samples with a bottom electrode grown on the surface of the substrate, a metal-dielectric-metal (MIM) structure capacitor is obtained.

8. The use of in-situ growth of an ultra-thin aluminum oxide protective layer on the surface of a wurtzite aluminum nitride-based film according to claim 7, characterized in that: The top electrode is made of one of the highly conductive metals Au, Pt, Al, Cu and TiN.

9. The use of in-situ growth of an ultra-thin aluminum oxide protective layer on the surface of a wurtzite aluminum nitride-based film according to claim 7, characterized in that: The thickness of the top electrode is 80-150nm.

Citation Information

Patent Citations

  • Method for sputtering and deposition of aluminum nitride piezoelectric thin film on flexible substrate through room-temperature reaction

    CN102383095A

  • Piezoelectric thin film element

    JP2009130182A